(untitled) (Teología, 2018)
Contemporary and confidant of Francisco de Sales, Pedro de Bérulle was born in France in 1575. His work is located in the first half of the 17th century. Being, rather, a spiritual author, his writings have not ceased to manifest a theological density. Among his books stands Grandeurs de Jésus (1623), considered his masterpiece, with a text that combines dogmatic approaches and mystical aspects. The present article tries to expose the pneumatology found in this work where, in general, a clear theology of the incarnation is presented. This theology is inserted in a Trinitarian framework, with a very focused attention on the relationship of the first two Persons. The person and role of the Holy Spirit is not present, but with a conception that allows us to glimpse the limits of the Berullian thought, typical of the theology of the time. The author approaches a balance from the perspective of contemporary theology that helps to better perceive the strengths and weaknesses of the pneumatology of the main reference of the French School of spirituality.